Component sizing optimization of plug-in hybrid electric vehicles with the hybrid energy storage system. (1st February 2018) - Song, Ziyou; Zhang, Xiaobin; Li, Jianqiu; Hofmann, Heath; Ouyang, Minggao; Du, Jiuyu
Abstract: The Pontryagin's minimum principle is utilized in this paper to determine the best solution of component sizing and energy management strategy for a plug-in hybrid electric vehicle which is equipped with a hybrid energy storage system. The hybrid energy storage system, including batteries and supercapacitors, is an effective solution to extend battery life span and reduce the vehicle operating cost. The operating costs of different hybrid energy storage system candidates, including fuel cost, electricity cost, and battery degradation cost over 6 consecutive China bus driving cycles, are minimized by using a 2-dimensional Pontryagin's minimum principle algorithm proposed in this paper. The proposed Pontryagin's minimum principle algorithm not only determines the optimal energy management strategy, but also globally finds the optimal battery and supercapacitor sizes. It is shown that the operating cost strictly decreases with increasing battery and supercapacitor sizes. In addition, simulation results show that the operating cost is reduced by up to 28.6% when compared to a conventional hybrid powertrain without supercapacitors. Thus the effectiveness of adopting supercapacitors in plug-in hybrid electric vehicles is verified. Highlights: The performance of the PHEV with a hybrid energy storage system is analyzed. The Pontryagin's minimum principle is utilized to solve the optimization problem. Optimal component sizes and energy management strategy are obtained simultaneously. The operation cost can be reduced by 28.6% when the SC pack is adopted in the PHEV.